Impact of Impurities on Crystallization and Product Quality: A Case Study with Paracetamol - Stephanie J. Urwin; Stephanie Yerdelen; Ian Houson; Joop H. ter Horst (Crystals, 2021)
A thorough, systematic study into the effect that structurally related impurities have on both the process and product quality during the crystallization of an active pharmaceutical ingredient is presented. The presence of acetanilide and metacetamol influences the crystallization and product quality of paracetamol. Where high concentrations of either impurity were present in the crystallization feed, product recovery decreased by up to 15%. Acetanilide is included in the final product through adsorption onto the particle surface in concentrations up to 0.79 mol%, which can be reduced to acceptable levels through product reslurrying. The presence of metacetamol results in much higher concentrations—up to 6.78 mol% in the final product, of which approximately 1 mol% is incorporated into the crystal lattice, resulting in the perturbation of the unit-cell dimensions. The incidental crystallization and subsequent isolation of metastable Form II paracetamol increased product purity in the presence of a low metacetamol concentration. This metastable product converts to stable paracetamol Form I through reslurrying, offering an efficient metacetamol impurity rejection route. The morphology of the product is modified consistently by both impurities. An elongation of the normal prismatic shape is observed, which in the extreme case of high metacetamol contamination results in the isolation of fine, fragile needles. This problematic morphology is also improved by a reslurrying of the crystallization product to give a more equilateral shape. This systematic study of the influence of acetanilide and metacetamol on the crystallization of paracetamol builds a well-rounded picture of the concomitant impact of impurities on the principal quality attributes of a crystallization product.